Growth Effects of Flat-Rate Taxes - Stokey, Nancy L.; Rebelo, Sergio (Journal of Political Economy, 1995)
Recent estimates of the potential growth effects of tax reform vary wildly, ranging from zero to eight percentage points. Using an endogenous growth model, the authors assess which model features and parameter values are important for determining the quantitative impact of tax reform. The quantitative estimates in several recent papers are compared with each other and with some of the evidence from U.S. experience. The authors find that Robert Lucas's conclusion, that tax reform would have little or no impact on the U.S. growth rate, is theoretically robust and consistent with the evidence. Copyright 1995 by University of Chicago Press.